Central giant cell granuloma of the jaws and giant cell tumor of long bones: an immunohistochemical comparative study - Maria do Socorro Aragão; Marta Rabello Piva; Cassiano Francisco Weege Nonaka; Roseana de Almeida Freitas; Lélia Batista de Souza; Leão Pereira Pinto (University of São Paulo, 2007)
OBJECTIVE: This study investigated whether some components of the extracellular matrix and CD68 expression may drive the differences between the central giant cell granuloma (CGCG) of the jaws and giant cell tumor (GCT) of long bones, which present distinct evolution and clinical behavior. MATERIAL AND METHODS: Eight cases of CGCG and 7 cases of GCT were selected and immunohistochemically analyzed to verify the pattern of expression of CD68, tenascin (Tn) and fibronectin (Fn). RESULTS: A large number of the mononuclear cells and multinucleated giant cells CD68+ was observed in both of the studied lesions, indicating histiocyte/ macrophage origin. Seven cases of CGCG of the jaws showed intense staining of Fn, with uniform distribution predominantly. In all 7 cases of GCT of long bones the Fn displayed intense expression, with distribution pattern varying from uniform to reticulate/fibrillar. Six cases of CGCG were intensively stained by Tn, presenting focal expression in half of specimens, and reticulate/ fibrillar pattern of expression in 4 cases. All cases of GCT of the long bones presented intense expression of Tn, uniform distribution, and reticulate/fibrillar pattern of expression in four cases. CONCLUSIONS: The immunoexpression of CD68 in mononuclear cells and multinucleated giant cells and staining patterns of Fn and Tn were similar in both entities. These findings indicate that these proteins could not be used to explain the differences between the CGCG of the jaws and GCT of the long bones.